Agent in place - Greaney, Mark (Greaney, Mark. Gray Man novel., 2018)
"The Gray Man is back in another nonstop international thriller from #1 New York Times bestselling coauthor of Tom Clancy's Jack Ryan novels Court Gentry is back in action. This time he's working on behalf of a well-connected group of Syrian expats to secure the Syrian president's mistress so they can use her to bring down the president's regime. But the expats' plan goes awry when it's discovered the mistress has a baby--the Syrian president's only male heir--hidden away in a Damascus safe house. Court goes after the baby, a decision that comes at the price of the mistress's life. The expat organization deems the boy now useless to their cause and refuses to protect him against the Syrian first lady and the notorious Swiss assassin in her employ. With no support on the way, Court realizes he'll have to take down the Syrian president himself if he and the boy are going to make it out alive."--